Identification the students’ pronunciation problems in pronouncing –ed ending at English Study Program of IAIN Bone - Nunu Wahyuni; Muhammad Zuhri Dj.; Hasriati Nur (International Journal of Research on English Teaching and Applied Linguistics, 2021)
This paper presents research about “Identification the Students’ Pronunciation Problems in Pronouncing –ed ending at English Study Program of IAIN Bone”. The sample consists of 5 students at the third semester in IAIN Bone. This research uses qualitative method by analyzing data using observation and interview. This paper aims to show the problems that students faced in pronouncing the –ed ending words. The result showed that most of the students were difficult to pronounce the –ed ending words correctly. They did not know how to pronounce and differentiate the words with final –ed, -d, or -t. The problems encountered by the students in pronouncing –ed ending caused by their lack of knowledge of the pronunciation of –ed ending. It is also possible that they do not know the theory well, and they are not able to practice it orally. So, the researchers concluded that there are some problems affecting the students’ ability to pronounce the –ed ending words. It because the students could not differentiate which one is final of /d/ id / and t/, the students also have lack of knowledge about –ed ending words.